“During the interview, the interpreter will provide a faithful translation.” The potentials and pitfalls of researchinginterpreting in immigration, asylum, and police settings: methodology and research paradigms - Pöllabauer, Sonja (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article presents a bibliometrical survey of an extensive corpus of research on interpreting in immigration, asylum andpolice settings. The article takes stock ofpast research andpoints towards questionsforfurther research. The corpus of relevant literature is grouped according to the authors’ disciplinary background, and examined on the basis of a bibliometrical analysis with respect to the authors’ affiliation, type(s) ofpublication, date(s) of publication, methodology, and predominant paradigms and topics. The survey also investigates the different analytical (mainly discourse analytical) approaches that have been used to analyse these kind of interpreter-mediated interviews